Interações dinâmicas no crescimento de tungue e cana-de-açúcar em sistemas agroflorestais - Schwerz, Felipe (2017)
The aim of the study was to evaluate the influence of meteorological variables on the growth of Tungue and its implications on the growth and productivity of sugarcane in agroforestry systems. The research was conducted from 2011 to 2016, in the city of Frederico Westphalen, Rio Grande do Sul, Brazil, with geographic location 27 ° 22'S, 53 ° 25'W and 480 m altitude. The experimental design was a randomized complete block with three replications. The species Tungue (Aleurites fordii) and Sugarcane (Saccharum officinarum L.) were used to compose the agroforestry systems. The trees were distributed in two arrangements of agroforestry systems, designated I and II. In the system I, trees were distributed in rows spaced at 12m; the sugarcane was distributed in eight rows, arranged in corresponding intervals between tree rows. In the system II, trees were grown in rows spaced at 6m; the sugarcane was distributed in four rows arranged in correspondence with intervals between tree rows. For the monocrop system with sugarcane, the plants were distributed in six rows with 12 meters length. In both systems, the cultivate sugarcane was the IAC 87-3396, which was distributed in spacing 1.20m. Both lines of sugarcane as the trees were oriented east-west direction. The tree variables analyzed were: stem diameter (cm), diameter at breast height (cm), plant height (m) and crown diameter (m). The productive variables analyzed in sugarcane were: stalk weight (Mg ha-1), stalk length (m), stalk diameter (mm), number of nodes, number of stalks, juice volume (m3 ha-1), sucrose content (g L-1) and sucrose quantity (Mg ha-1). Sugarcane growth variables evaluated: leaf area index (m2 m-2), absolute growth rate (g day-1), net assimilation rate (g m-2 day-1), radiation use efficiency (g MJ-1), biomass partitioning (g), total dry matter (g m-2), plant height (m), number of tillers, extinction coefficient and % of intercepted global radiation. The meteorological variables occurring during the study were obtained through Climatological the National Institute of Meteorology Station, located at 200 m from the study site, with geographic location 27°39'S and 53°43'W. The dynamic interactions between Tungue trees and meteorological variables were determinant for the growth and productivity responses of sugarcane cultivated in the understory. For the sugarcane production, the use of an intercropping system with 12x12m arrangements should be prioritized, because it promotes greater sugarcane yields when compared to a 6x6m intercropping system, since the quality of the sugarcane was not affected by the cultivation systems. In the future, from the moment that Aleurites fordii trees show a productive return, a new joint analysis of the data should be made in order to verify the suggested recommendation of the present research.